2007
DOI: 10.1590/s1677-55382007000200005
|View full text |Cite
|
Sign up to set email alerts
|

Perineural invasion by transitional cell carcinoma of the bladder in patients submitted to radical cystectomy: what is the prognostic value?

Abstract: Objective: Determine the prognostic value of perineural invasion (PNI) in patients with transitional cell carcinoma (TCC) of the bladder treated with radical cystectomy. Materials and Methods: From January 1993 to January 2005, 113 people were selected from 153 patients with TCC of the bladder treated with radical cystectomy. The association between the presence of PNI and other pathologic characteristics were analyzed through Fisher exact test. The Kaplan-Meier method was utilized to assess the survival curve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
1
1
0
1
Order By: Relevance
“…The latter is a more plausible explanation, considering the infrequent pattern of perineural invasion of transitional cell carcinoma [11]. In support of this, the MRI images from this patient demonstrate a plane of cleavage between the involved lymph node and obturator nerve ( Figure 5).…”
Section: Discussionsupporting
confidence: 63%
“…The latter is a more plausible explanation, considering the infrequent pattern of perineural invasion of transitional cell carcinoma [11]. In support of this, the MRI images from this patient demonstrate a plane of cleavage between the involved lymph node and obturator nerve ( Figure 5).…”
Section: Discussionsupporting
confidence: 63%
“…It was suggested that PNI with UCC might be accompanied by inferior prognosis, specifically for extravesical and LN-positive disease subsequent RC ( 15 ). On the other hand, Antunes et al identified PNI in 10 (8.8%) out of 113 patients and concluded that PNI did not constitute an independent factor of cancer-free and survival rate ( 16 ). This different finding across all articles might be due to variable cohort sizes and varied study populations.…”
Section: Discussionmentioning
confidence: 99%
“…Uma observação curiosa foi a frequência relativamente elevada da detecção de invasão perineural na nossa casuística (38 casos -62,3%), achado maior que em estudos prévios relatados, nos quais variam entre 6,8% e 47,7% (98). Mesmo com 38 casos exibindo a invasão perineural, nenhuma associação significativa foi observada com a expressão das MMPs, talvez devido à baixa importância desse achado morfológico no que diz respeito aos fatores de impacto do carcinoma urotelial, ou porque os endpoints mais adequados para tal avaliação sejam os critérios clínicos que referimos anteriormente quanto à invasão vascular.…”
Section: Invasão Neoplásica Perineuralunclassified